Investigation of miR-71, let-7-5p, and miR-2b-5p in lambs experimentally infected with Echinococcus granulosus: Preliminary insights into their diagnostic relevance - Celik, Figen; Tektemur, Ahmet; Simsek, Sami (Elsevier, 2025)
Cystic echinococcosis (CE), caused by the larval stage of Echinococcus granulosus sensu lato, remains a major public health and veterinary concern. This study investigated the diagnostic potential of three parasite-derived microRNAs (miR-71, let-7-5p, and miR-2b-5p) in the serum of experimentally infected lambs. Protoscoleces isolated from sheep liver hydatid cysts were used to infect puppies, from which viable eggs were harvested and administered to newborn lambs (n = 11); uninfected lambs (n = 3) served as controls. Weekly serum samples were collected and analyzed for microRNA expression using manual RNA extraction, reverse transcription, and real-time quantitative PCR (qRT-PCR). None of the evaluated miRNAs were detected in pre-infection or control sera (Ct>40), whereas post-infection expression (Ct<40) was observed at various time points. Notably, miR-71 was consistently expressed in all infected lambs between weeks 1-10 and 20-30. Let-7-5p and miR-2b-5p also showed dynamic expression profiles, particularly during early and late infection phases. These findings suggest that these circulating miRNAs could serve as promising non-invasive biomarkers for the early diagnosis and monitoring of CE. However, large individual variations were observed in the expression levels of all three miRNAs, which should be considered when interpreting their diagnostic potential.
Keywords: Echinococcus granulosus; Lamb; Biomarker; miR-71; let-7-5p; miR-2b-5p